ยุทธศาสตร์การพัฒนาหมู่บ้านต้นแบบในการอนุรักษ์ป่าสงวนแห่งชาตินากาย-น้ำเทิน: กรณีศึกษา บ้านโพนสะอาดเมืองคำเกิด แขวงบลิคำไซ สาธารณรัฐประชาธิปไตยประชาชนลาว - พลสีลา คุดสะหวาด (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
ยุทธศาสตร์การพัฒนาหมู่บ้านต้นแบบในการอนุรักษ์ป่าสงวนแห่งชาตินากาย-น้ำเทิน: กรณีศึกษา บ้านโพนสะอาดเมืองคำเกิด แขวงบลิคำไซ สาธารณรัฐประชาธิปไตยประชาชนลาว STRATEGY TO DEVELOP A MODEL VILLAGE IN CONSERVATION OF NAKAI-NAMTHEUN NATIONAL FOREST RESERVE: A CASE STUDY IN PHONSA-AAD VILLAGE, KHAMKEUT DISTRICT, BOLIKHAMXAI PROVINCE, LAO PEOPLE’S DEMOCRATIC REPUBLIC บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) เพื่อศึกษาบริบท สภาพปัญหา ความต้องการและแนวทางการพัฒนาหมู่บ้านต้นแบบในการอนุรักษ์ป่าสงวนแห่งชาตินากาย-น้ำเทิน บ้านโพนสะอาด เมืองคำเกิด แขวงบลิคำไซ สาธารณรัฐประชาธิปไตยประชาชนลาว 2) เพื่อสร้างยุทธศาสตร์การพัฒนาหมู่บ้านต้นแบบในการอนุรักษ์ป่าสงวนแห่งชาตินากาย-น้ำเทิน กลุ่มเป้าหมาย ภาครัฐจากเจ้าหน้าที่ผู้ดูแลคุ้มครองป่าสงวนและทรัพยากรป่าไม้ 8 คน และผู้อำนวยการโรงเรียนประจำหมู่บ้าน 1 คน รวม 9 คน และตัวแทนภาคประชาชนที่เป็นผู้นำของหมู่บ้านโพนสะอาด 19 คน รวมทั้งสิ้นจำนวน 28 คน โดยเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสัมภาษณ์เชิงลึก แบบสังเกต และการประชุมเชิงปฏิบัติการ ข้อมูลทำการวิเคราะห์ทั้งเชิงคุณภาพและเชิงปริมาณ สถิติที่ใช้ในการวิจัย ได้แก่ คือ เปอร์เซ็นต์ และ ค่าเฉลี่ย (Mean) นำเสนอโดยใช้การพรรณนาเชิงวิเคราะห์ ผลการวิจัยพบว่า 1. สภาพปัญหาที่เกิดขึ้นกับป่าสงวนแห่งชาตินากาย-น้ำเทิน ในปัจจุบัน พบว่าเกิดจากสาเหตุสำคัญ 2 ประการ ประกอบด้วย 1) ปัญหาทางตรง คือ (1) การลักลอบตัดไม้ทำลายป่า (2) การบุกรุกพื้นที่ป่าไม้เพื่อขยายพื้นที่ทำกินของประชาชน (3) การล่าสัตว์ป่า การเก็บหาของ และ 2) ปัญหาทางอ้อม คือ (1) ความยากจน (2) ความไม่แน่นอนของสภาพดินฟ้าอากาศ ทั้งนี้ ปัญหาที่พบได้รับการจัดอันดับตามผลกระทบต่อชุมชนตั้งแต่ระดับมากที่สุดไปจนถึงระดับน้อยที่สุด 2. แนวทางเพื่อแก้ปัญหาป่าสงวนแห่งชาตินากาย-น้ำเทิน จากการเรียงลำดับตามความสำคัญที่ควรดำเนินการอย่างเร่งด่วนตามลำดับก่อนหลัง และขีดความสามารถของชุมชน มีดังนี้ 1) ส่งเสริมอาชีพโดยใช้วัตถุดิบและภูมิปัญญาท้องถิ่น โดยใช้กองทุนหมู่บ้านให้การสนับสนุนการประกอบอาชีพ 2) สร้างเสริมความรู้ความเข้าใจและจิตสำนึกเกี่ยวกับการอนุรักษ์ทรัพยากรป่าไม้ให้กับประชาชนในหมู่บ้าน 3) ประชาสัมพันธ์การอนุรักษ์ทรัพยากรธรรมชาติและสิ่งแวดล้อมด้วยหลายรูปแบบ 4) ตักเตือนผู้บุกรุกในครั้งแรกที่ทำผิดกฎระเบียบ และลงโทษตามกฎหมายในครั้งต่อไป 5) ปฏิบัติกฎระเบียบการรักษาป่าสงวนแห่งชาติให้เข้มงวด 6) ฝึกอบรมคณะกรรมการอนุรักษ์ในการดูแลรักษาป่าสงวนแห่งชาติ 7) ให้ค่าตอบแทน เจ้าหน้าที่ผู้ปฏิบัติงาน เพื่อสร้างขวัญและกำลังใจ 8) ให้รางวัลแก่ผู้แจ้งเบาะแสการลักลอบตัดไม้ทำลายป่า และ 9) การมีส่วนร่วมของหน่วยภาครัฐ องค์กรเอกชน (ต่างประเทศ) และภาคประชาชน (ชาวบ้าน) ในการอนุรักษ์ทรัพยากรธรรมชาติและสิ่งแวดล้อม 3. ยุทธศาสตร์การพัฒนาหมู่บ้านต้นแบบในการอนุรักษ์ป่าสงวนแห่งชาตินากาย-น้ำเทิน ประกอบด้วย วิสัยทัศน์ พันธกิจ ประเด็นยุทธศาสตร์ เป้าประสงค์ เป้าหมาย กลยุทธ์ มาตรการ มี 8 โครงการ คือ 1. โครงการอาสาสมัครพิทักษ์ป่าสงวนแห่งชาติ 2. โครงการสร้างความเข้มแข็งแก่หน่วยพิทักษ์รักษ์ป่าสงวน 3. โครงการเพิ่มประสิทธิภาพการปฏิบัติงานของหน่วยงานที่เกี่ยวข้อง 4. โครงการการอบรมให้ความรู้ความเข้าใจ และการมีส่วนร่วมของประชาชนในการอนุรักษ์ป่าสงวนแห่งชาตินากายน้ำเทิน 5. โครงการการอบรมเยาวชนเพื่อการอนุรักษ์ทรัพยากร 6. โครงการการส่งเสริมการเลี้ยงสัตว์พื้นบ้านในชุมชน 7. โครงการการผลิตและใช้ปุยชีวภาพ 8. โครงการหมู่บ้านต้นแบบในการอนุรักษ์ป่าสงวนแห่งชาตินากาย-น้ำเทิน ABSTRACT The purposes of this study were: 1) to investigate the context, problem state, needs and guidelines of developing a model village in conservation of Nakai-Namtheun National Forest Reserve, Phonsa-aad village, Khamkeut district, Bolikhamxai province, Lao People’s Democratic Republic, 2) to create a strategy to develop a model village in conserving the Nakai-Namtheun National Forest Reserve. The target group of 28 as selected by purposive sampling comprised: 1) 8 government officers whose duties were to protect the forest reserve and its resources and 1 school director in the research area totaling 9 people, and 2) 19 leaders of Phonsa-aad village; and the total amounted to 28 people, The instruments used were an in-depth interview, an observation form, and a workshop. Both qualitative and quantitative data were analyzed. Statistics used were percentage and mean. Presentation was carried out through analytical description. The findings were as follows: 1. The current problem state incurred with the Nakai-Namtheun National Forest Reserve has been found from 2 significant causes: 1) from direct problems: (1) illegal deforestation, (2) encroachment of forest areas to expand the arable area of the people, (3) hunting wild lives and gathering of forest products; and 2) from uncertainty of the weather. The problems have been ranked according to the impact on the community as arranged from the highest to the lowest levels respectively. 2. The guidelines for solving the problems of the Nakai-Namtheun National Forest Reserve as arranged in order of importance that should be implemented urgently and based on the capability of the community comprise the following: 1) promoting the use of raw materials and local knowledge by using the village fund to support the people to make their living, 2) enhancing the understanding and awareness of conserving the forest resources to the people in the village, 3) exercising the variety of public relations of the natural resources and environment conservation, 4) warning intruders who break the rules in the first place and punishing them according to the law in the next time, 5) being in strict compliance with regulations of maintaining the National Forest Reserve, 6) training the Conservation Committee in care of the National Forest Reserve, 7) providing compensation to those who are on duty for building morale, 8) giving a reward to the whistle-blower who makes a report of illegal deforestation, and 9) having joint work between the government agencies, the international private sector, and the local public in conservation of the natural resources and environment. 3. The strategy to develop a model village in conservation of the Nakai-Namtheun National Forest Reserve comprises: vision, missions, strategic issues, objectives, targets, strategies and measures. The strategy has 8 projects, namely: 1) people’s volunteering for protection of the National Forest Reserve, 2) strengthening the unit of the National Forest Reserve protection, 3) optimizing the performance of the agencies involved, 4) giving a train of knowledge, understanding and participation to the people concerning the forest reserve conservation, 5) giving a train of knowledge, understanding and participation to the youth concerning the forest reserve conservation, 6) promotion of raising local animals in the community, 7) producing and using the organic fertilizer, and 8) creating a model village in conservation of the Nakai-Namtheun National Forest Reserve.